Diversity Oriented Synthesis of Allocolchicinoids with Fluoro and/or Oxygen Substituent(s) on the C‐Ring from a Single Common Intermediate1. Issue 8 (16th February 2016) - Takubo, Keita; Furutsu, Kazunori; Ide, Takafumi; Nemoto, Hiroyuki; Ueda, Yuko; Tsujikawa, Kazutake; Ikawa, Takashi; Yoshimitsu, Takehiko; Akai, Shuji
Abstract: Allocolchicinoids, with a distinct polyoxygenated dibenzocycloheptane skeleton, attract much attention as potential candidate anticancer drugs. In this study, eight C‐ring fluorinated analogues of allocolchicinoids, seven C‐ring oxygen‐substituted analogues, and known compounds N ‐acetylcolchinol and NSC 51046 were synthesized as racemates from a single common intermediate by using either the deoxyfluorination/migration domino reaction or acid‐promoted migration as the key step. Among the products obtained, some of the fluorinated derivatives strongly inhibited the growth of prostate DU145 and pancreas Panc 1 cancer cell lines with efficacy comparable to or better than those of N ‐acetylcolchinol and NSC 51046. They were also less toxic against a non‐cancerous cell line than the known compounds were. Abstract : Eight C‐ring fluorinated analogues of allocolchicinoids, seven C‐ring oxygen‐substituted analogues, and known compounds N ‐acetylcolchinol and NSC 51046 were synthesized from a single common intermediate by using either the deoxyfluorination/migration domino reaction or acid‐promoted migration as the key step. Some fluorinated compounds showed high cytotoxicity against prostate cancer cells.